2016
DOI: 10.4238/gmr.15027711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GSTM1, GSTT1, and GSTP1 IIe105Val polymorphisms on susceptiblity to gestational diabetes mellitus

Abstract: ABSTRACT. We investigate the role of the GSTM1, GSTT1, and GSTP1 IIe105Val genetic polymorphisms in the susceptibility to gestational diabetes mellitus. A total of 223 pregnant women with gestational diabetes mellitus and 265 healthy pregnant women were examined at The Second Affiliated Hospital of Shaanxi University of Chinese Medicine from May 2013 to November 2013. Genotyping for detection of GSTM1, GSTT1, and GSTP1 IIe105Val polymorphisms was conducted using the restriction fragment length polymorphismpoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The dispersal of genotypes was in alignment with Hardy-Weinberg equilibrium. Similar to other studies, in a Chinese population, GSTP1 IIe105Val polymorphisms did not have an impact on the risk of gestational diabetes mellitus [25]. Li et al [26] found that the GSTP1 IIe105Val polymorphism was not associated with an elevated risk of gestational diabetes mellitus in a Chinese population.…”
Section: Modelsupporting
confidence: 73%
“…The dispersal of genotypes was in alignment with Hardy-Weinberg equilibrium. Similar to other studies, in a Chinese population, GSTP1 IIe105Val polymorphisms did not have an impact on the risk of gestational diabetes mellitus [25]. Li et al [26] found that the GSTP1 IIe105Val polymorphism was not associated with an elevated risk of gestational diabetes mellitus in a Chinese population.…”
Section: Modelsupporting
confidence: 73%
“…For the children of mothers with gestational diabetes, complications that are directly related to kidney disease include increased rates of congenital anomalies of the kidneys and urinary tract (46), metabolic syndrome (47), and early-onset cardiovascular disease (48). The GSTM1 null allele has been reported to associate with higher odds of gestational diabetes in several studies (49)(50)(51), but a study by Orhan et al (52) reported no such association in a Turkish population. More studies are needed to determine the influence of gene-gene and gene-environment interactions on the effect of the GSTM1 genotype in different human populations.…”
Section: Risks Associated With Gstm1 Deletions In the Prenatal Period...mentioning
confidence: 99%